2012
DOI: 10.4081/mrm.2012.596
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breathing maneuver and sitting posture on muscle activity in inspiratory accessory muscles in patients with chronic obstructive pulmonary disease

Abstract: Background: To determine the influence of breathing maneuver and sitting posture on tidal volume (TV), respiratory rate (RR), and muscle activity of the inspiratory accessory muscles in patients with chronic obstructive pulmonary disease (COPD). Methods: Twelve men with COPD participated in the study. Inductive respiratory plethysmography and surface electromyography were used to simultaneously measure TV, RR, and muscle activity of the inspiratory accessory muscles [the scalenus (SM), sternocleidomastoid (SCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 16 publications
4
11
1
1
Order By: Relevance
“…To our knowledge, this study is the first to identify the effect of breathing patterns and body positions on both total and regional lung volumes in older adults. Overall, the increase in absolute chest wall volumes and associated chest wall diameters during the PLB compared to the QB performed within the same body positions observed in our older adults were in line with those previously reported in patients with COPD [13,17,21–24] . The increase in total and regional chest wall volumes has been shown to provide better gas exchange in the lungs and reduce the sensation of dyspnea [13,21] .…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this study is the first to identify the effect of breathing patterns and body positions on both total and regional lung volumes in older adults. Overall, the increase in absolute chest wall volumes and associated chest wall diameters during the PLB compared to the QB performed within the same body positions observed in our older adults were in line with those previously reported in patients with COPD [13,17,21–24] . The increase in total and regional chest wall volumes has been shown to provide better gas exchange in the lungs and reduce the sensation of dyspnea [13,21] .…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, the results of the study indicated that the magnitude of the anterior-to-posterior movement of the upper ribcage was greater in forward-leaning postures than in upright ones. The results were moreover consistent with those of Kim et al (2012). Although patients with chronic obstructive pulmonary disease (COPD) composed their study's sample, both their and our collection protocols allow evaluating the effect of gravity action on the mechanics of breathing.…”
Section: Discussionsupporting
confidence: 76%
“…Normally, the trunk is stabilized, and accessory respiratory muscles move the vertebral column, arm, head, and pelvis on the trunk (Starr & Dalton, 2011). When the shoulder girdle is fixed by arm support, the ribcage becomes the mobile segment (Banzett et al, 1988;Kim et al, 2012). The effect of the muscle's pull is transferred to the ribcage, and the SMC and Sc pull the sternum and the first two ribs, thereby increasing the thoracic diameter by moving the ribcage upward and outward in a pump-handle motion (Starr & Dalton, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations